Lipase diffusion in oil-filled, alginate micro- and macrobeads. (December 2018) - van Leusden, P.; den Hartog, G.J.M.; Bast, A.; Postema, M.; van der Linden, E.; Sagis, L.M.C.
Abstract: Triglycerides, which are broken down in the lower part of the intestinal tract, give a stronger ileal brake feedback, resulting in a feeling of satiety and causing people to eat less. The digestion of triglycerides into fatty acids by lipase in the intestine can be delayed by encapsulating oil droplets. In this study the release of fatty acids and oil droplet breakdown in a simulated intestinal system was investigated, for oil droplets encapsulated in alginate micro- (10.7 μm) and macrobeads (1.77 mm). It was found that fatty acid release rate was greatly decreased by encapsulating the oil droplets into an alginate matrix compared to loose droplets. Microscopic imaging of the breakdown of the oil droplets showed a sharp front moving from the bead interface to the centre of the bead, and the change in position of the front scaled linear with time. The motion of the front is well described by combining the mass balance for lipase with a Maxwell-Cattaneo type equation, for the mass flux vector. The front in microbeads seemed to move slightly slower (0.15 (±0.04) μm per minute) than for the macrobeads (0.20 (±0.02) μm per minute). The release of free fatty acids in microbeads was faster than in macrobeads, despite the slower front movement, because of the larger amount of surface area available. Graphical abstract: Highlights: Encapsulation of oil droplets in an alginate, hydrogel matrix delays oil digestion. Oil digests faster in micro-than in macrobeads because of the larger surface area. A visible front of digestion moves from the interface of the bead to the centre. The front progression is described by a Maxwell-Cattaneo type equation.